Eviota karaspila, a new gobiid fish from Fiji (Teleostei: Gobiidae) - Greenfield, David W.; Randall, John E. (Zootaxa, 2010)
A new species of goby, Eviota karaspila, most similar to E. melasma, is described from Fiji. It differs from E. melasma in having a larger eye and in live coloration and from E. smaragdus in having a more slender caudal peduncle, and in coloration.